2018
DOI: 10.3390/act7040078
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Response of Four-Bar Linkage Microgrippers with Bidirectional Electrostatic Actuation

Abstract: This paper presents both an experimental and a numerical study concerning the mechanical response of a silicon microgripper with bidirectional electrostatic actuation to externally applied excitations. The experimental set-up is composed of a probe station equipped with mobile probes that apply contact forces. This part of the investigation aims to test the device’s mechanical resistance, its mobility capability and possible internal contacts during the system deformation. The second part of the paper is dedic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…More experimental work and simulations have recently shown that the total number of flexures is related to the energy required to deform the structure from neutral to working configurations. Therefore, microgrippers with only one CSFH pair, operated by one pair of rotary-comb drives [ 33 ], presented, at the same applied voltage, a range of motion wider than those embedding several CSFHs, as, for example, planar 3-DoF microstages [ 34 ] or four-bar linkage microgrippers with bidirectional comb drives [ 35 ]. In the latter microsystems, comb drives are arranged in such a way that it is possible to induce either clockwise or counterclockwise jaw rotations.…”
Section: Introductionmentioning
confidence: 99%
“…More experimental work and simulations have recently shown that the total number of flexures is related to the energy required to deform the structure from neutral to working configurations. Therefore, microgrippers with only one CSFH pair, operated by one pair of rotary-comb drives [ 33 ], presented, at the same applied voltage, a range of motion wider than those embedding several CSFHs, as, for example, planar 3-DoF microstages [ 34 ] or four-bar linkage microgrippers with bidirectional comb drives [ 35 ]. In the latter microsystems, comb drives are arranged in such a way that it is possible to induce either clockwise or counterclockwise jaw rotations.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, new emerging MEMS-Technology based instruments for biomedical and surgical applications have been developed. In fact, based on a new concept hinge [28,29], a class of different microgrippers, equipped with rotary comb-drives, has been developed [30][31][32][33], also in significant environments [34], and fabricated [35,36]. Thanks to their size, these instruments are expected to be employed in surgery and diagnostics.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental activities described in this paper much owe to the past years, during which a new microgripper has been developed by the team, from the early stage of concept design to the operational testing, through the following phases: design [46,47,48], optimization [49,50,51], simulation and control [52], fabrication [53,54], mechanical characterization [55], actuation design [56] and testing [57], and, finally, operational [58] and functional [59,60,61] testing. Although the results of the present investigation (see Section 3) refer to the manipulation of micro objects whose overall size spans from 20 μm to 165 μm, there are some efforts to develop fabrication methods [62] toward the extreme miniaturization of microgrippers that could grasp even objects downsized by about one more order of magnitude.…”
Section: Introductionmentioning
confidence: 99%